Environmental modification of western equine encephalomyelitis infection in the snowshoe hare (Lepus americanus). - Kiorpes, A L (1975)
The snowshoe hare (Lepus americanus) could be infected with western equine encephalomyelitis (WEE) virus and produce a viremia. Furthermore, viremia in hares exposed to variable climatic conditions differed significantly from viremias seen in the control animals held at constant temperatures. The viremia duration and titer were increased in animals subjected to fluctuating temperature and humidity. The time of onset of viremia was accelerated. Antibody response also increased in animals exposed to varying temperatures when compared with controls held at constant temperature and humidity. Snowshoe hares were studied at two distinct seasonal periods: winter, before reproductive activity; and summer, during reproductive midseason. Winter animals experienced greater viremia than did summer hares when exposed to fluctuating temperatures, suggesting a seasonality in the hare's susceptibility to host modification by environmental influences. These findings implicate the snowshoe hare as a possible mammalian amplifying host for WEE virus in the boreal forest.